The reception of D.H. Lawrence in Europe - Jansohn, Christa; Mehl, Dieter (London : Continuum, 2007)
The intellectual scope and cultural impact of British and Irish writers cannot be assessed without reference to their 'European' fortunes. This collection of essays records the ways in which D.H. Lawrence's work has been received, translated and published in different area's of Europe.
14 Feeding a Fire of Change: The Reception of D.H. Lawrence in Sweden15 In Hamsun's Shadow: The Reception of D.H. Lawrence in Norway; 16 The Reception of D.H. Lawrence in Denmark; Bibliography; Index; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; Q; R; S; T; U; V; W; Y; Z.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Lawrence, D. H. -- 1885-1930 -- Appreciation -- Europe; Lawrence, D. H. -- 1885-1930 -- Criticism and interpretation -- History; Lawrence, D. H. -- 1885-1930; Lawrence, David H; European literature -- English influences; Littérature européenne -- Influence anglaise; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Art appreciation; Europe; Literatur; Rezeption; Europa; Receptie; Europa (geografie); Geschichte; Criticism, interpretation, etc; History